On two-door three-dimensional container packing problem under home delivery service. (2nd April 2016) - Lin, Chun-Cheng; Kang, Jia-Rong; Liu, Wan-Yu; Li, Cheng-Chi
Abstract : This paper considers the three-dimensional container packing problem (3DCPP) under home delivery service, which predetermines an ordering of delivering ordered cargo boxes to customers, and aims to load a subset of those boxes according to the delivery ordering into a 3D car container with maximal utilization ratio of the container space while prohibiting the process of delivering cargos to each customer from unloading and subsequent reloading of boxes. In practice, cargos can be taken out from not only the rear door of the delivery container but also the side door. Nonetheless, the previous research only considered the case with only a single door. Therefore, this paper establishes the model for the two-door 3DCPP under home delivery service. Furthermore, the rule of invisible and untouchable items and the subvolume-based approach for the one-door problem are extended to resolve the two-door problem. Last, simulation analysis verifies performance of our approach.